2000
DOI: 10.1007/s002770000182
|View full text |Cite
|
Sign up to set email alerts
|

E-selectin and very late activation antigen-4 mediate adhesion of hematopoietic progenitor cells to bone marrow endothelium

Abstract: Adhesion of CD34+ hematopoietic progenitor cells (HPCs) to sinusoidal endothelium probably plays a key role in homing of transplanted CD34+ HPCs to the bone marrow (BM). We have investigated the role of various adhesion molecules in the interaction of purified CD34+ HPCs derived from BM or peripheral blood (PB) and a human BM-derived endothelial cell line. Adhesion of CD34+ HPCs to endothelial cells was measured with the use of a double-color flow microfluorimetric adhesion assay. In this assay, adhesion is me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…It was previously shown by our group and others that the ␤1 integrins very late Ag (VLA)-4 and VLA-5 are required for efficient transendothelial migration of CD34 ϩ cells (2,11,41,42). Therefore, we investigated which adhesion molecules that are known ligands for VLA-4 and VLA-5 mediate the migration of CD34 ϩ cells across HBMECs.…”
Section: Role Of Icam-1 and Vcam-1 In Ve-cadherin-mediated Transmigramentioning
confidence: 99%
“…It was previously shown by our group and others that the ␤1 integrins very late Ag (VLA)-4 and VLA-5 are required for efficient transendothelial migration of CD34 ϩ cells (2,11,41,42). Therefore, we investigated which adhesion molecules that are known ligands for VLA-4 and VLA-5 mediate the migration of CD34 ϩ cells across HBMECs.…”
Section: Role Of Icam-1 and Vcam-1 In Ve-cadherin-mediated Transmigramentioning
confidence: 99%
“…In fact, BM microvessels express E-selectin constitutively, while E-selectin is inducible on endothelial linings of inflamed tissues and of bronchial mucosa, a common PCa target tissue (7)(8)(9). Mechanistically, an identical traffic control axis involving selectins is well-known in the extravasation of hematopoietic progenitor cells (HPC) into BM (10,11). HPC rolling on E-and platelet (P)-selectin is regulated by sLe X -bearing glycoforms of CD44 (HCELL), PSGL-1 and glycolipids (10,12,13).…”
mentioning
confidence: 99%
“…2B), however, C17.2-luc cell recruitment to activated normal endothelium was blocked completely by function blocking antibodies to α 4 -integrin, suggesting that VLA-4 is the critical receptor for C17.2-luc cell recruitment to inflamed endothelium, consistent with its role in recruitment of hematopoietic progenitors to bone marrow endothelium. 10 Function blocking antibodies to any of the adhesion molecules examined, did not, however, have any effect on C17.2-luc cell recruitment to tumor endothelium (Fig. 4), suggesting the presence of additional adhesive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Neural cells have been demonstrated to express CD34, 27 commonly associated with hematopoietic stem cells and endothelial cells, and recent DNA microarray analysis has confirmed that neuronal precursors express Ephrin B2 and neuropilin, whereas glial precursors express CD44 and CXCR4, the receptor for the CXC chemokine, SDF-1. 28 The recruitment of hematopoietic progenitor cells has been shown previously to be mediated via selectins, [8][9][10][11]12 and VLA-4, 10,11 and recently it was demonstrated that recruitment of embryonic progenitors to tumor vessels was mediated via E-and P-selectins and PSGL-1. 29 Similarly SDF-1 is known to be chemotactic for CD34+ progenitors, 21,30 however, to date, no studies have dissected the specific molecules that mediate neuronal progenitor recruitment to underlying vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation